BLOCKCHAIN TECHNOLOGY IN THE DIGITAL MARKETING SECTOR - Nico Djundharto Djajasinga; Bagus Setya Rintyarna; Siti Nurhayati; Saida Zainurossalamia ZA; Intan Nurrachmi (LPPM STIE Muhammadiah Bandung, 2022)
Similar to the internet, blockchain technology could be the next digital revolution. Blockchains offer tremendous potential, which is why numerous businesses have begun implementing this technology. With the internet enabling the transmission of information, blockchain enables the communication of value. Blockchain is not only associated with cryptocurrencies; thanks to this technology, businesses may increase brand value. As blockchain is a developing technology, there are still numerous possible applications. This has prompted us to investigate the viability of implementing blockchain in the marketing industry. This study examines the application of blockchain technology in the digital marketing industry. This study employs a qualitative approach and descriptive methodologies. The survey results indicate that blockchain is very effective in digital marketing since it may increase consumer trust. This is because blockchain technology guarantees the honesty and integrity of data. In addition, blockchain technology eliminates intermediaries, making the marketing process more straightforward, cheaper, faster, and more accessible.